THE ACTIVITIES OF DISASTER - AFFECTED HOUSE IDENTIFICATION IN TANGERANG DISTRICT - Sarjono Puro; Edison Hatoguan Manurun; Muji Indarwanto (International Journal of Engagement and Empowerment, 2021)
Home is a basic human need. A house that is easy to interpret is a real house where a family can live inside. It is supported by the availability of clean water, lighting, and proper environmental equipment to meet basic needs from plumbing to sewerage. It is also safe for residents' activities that residents can objectively accept. Natural disasters are caused by nature in earthquakes, tsunamis, landslides, droughts, hurricanes, floods, and volcanic eruptions that affect people's homes. Rehabilitation activities for houses affected by disasters such as hurricanes, floods, and other disasters carried out by the Tangerang Regency Perkim Service Referring to the Law on the Regional Head of the National Disaster Management Agency of 2008 Number 11 are intended to fulfill the rehabilitation requirements. The important identification activities are carried out to ascertain whether the disaster-affected houses deserve assistance. The identification results become a reference in determining recommendations. Follow up on requests by drawing up plans and a schedule for the construction of the rehabilitation program